Audience Matters: Multimodal Projects Across Three International Case Studies - Schrum, Kelly; Majury, Niall; Simonelli, Anne Laure; Bodgewiecz, Sarah (Teaching and Learning Inquiry, 2022)
There is growing attention to student assessments designed to reach beyond the classroom, including assessments with an immediate or future audience. The impact of audience, however, has not been examined in multimodal assessments across continents, institutions, disciplines, and teaching contexts. Using qualitative data, this article examines the impact on student learning of incorporating audience and awareness of audience in diverse settings through multimodal projects. These include a core assignment in an interdisciplinary, semester-long graduate class in the United States, a year-long capstone project for geography undergraduates in Northern Ireland, and a supplemental assignment for graduate and undergraduate biology students in Norway. This article investigates the impact of audience through multimodal assessments across these three settings and concludes that it can positively influence student learning, motivation, and skill development.